Exploring emergent literacy development in a second language: A selective literature review and conceptual framework for research. (March 2015) - Chan, Lydia LS; Sylva, Kathy
While there have been reviews over the past decade of studies examining second-language (L2) acquisition and also emergent literacy development, these related bodies of knowledge have not generally been considered together in relation to the education of very young English-language learners. This paper attempts to do so in a selective manner by proposing a preliminary conceptual framework for second language emergent literacy development, thus paving the way for future research. The literature on the emergent literacy of native English speakers is first outlined, followed by a discussion of the general effects of bilingualism and cross-linguistic transfer, with the special case of Hong Kong children serving as an illustrative example. Finally, potential environmental influences are explored, with a focus on the home literacy environment.